Two new species of Yaginumaella (Araneae, Salticidae) from Wuling Mountain, China - Li, Dan; Wang, Cheng; Irfan, Muhammad; Peng, Xian-Jin (European Journal of Taxonomy, 2018)
The present paper deals with two new species, Yaginumaella pulchella sp. nov. and Yaginumaella hubeiensis sp. nov. Distributional data, as well as illustrations of body and copulatory organs, are provided. Descriptions of their morphology are given. The differences between the new species and their related taxa are discussed.